2021
DOI: 10.3390/en14144265
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Dynamic Linkage between Renewable Energy Consumption, Globalization, and Environmental Degradation in South Korea: Does Technological Innovation Matter?

Abstract: The present research assesses the influence of globalization and technological innovation on CO2 emissions in South Korea as well as taking into account the role of renewable energy consumption and energy consumption utilizing datasets between 1980 and 2018. The autoregressive distributed lag (ARDL) bounds testing method is utilized to assess long-run cointegration. The outcome of the ARDL bounds test confirmed cointegration among the series. Furthermore, the ARDL reveals that economic growth, energy consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 42 publications
(55 reference statements)
1
15
0
Order By: Relevance
“…Since nonrenewable energy use has exacerbated global warming, the international community is focusing on a sustainable development plan that calls for the adoption of green sources of energy (Ahmad et al, 2021 ). Renewable energy is an important component of cost-effective and technically possible GHG reduction solutions (Coelho et al, 2021 ). By lowering the dependence on fossil fuels, REN can aid in abating emission and maintaining energy security.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Since nonrenewable energy use has exacerbated global warming, the international community is focusing on a sustainable development plan that calls for the adoption of green sources of energy (Ahmad et al, 2021 ). Renewable energy is an important component of cost-effective and technically possible GHG reduction solutions (Coelho et al, 2021 ). By lowering the dependence on fossil fuels, REN can aid in abating emission and maintaining energy security.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Moreover, the studies of Koengkan et al (2020), Pata (2021), and Khan et al (2019) disclosed CO 2 -GLO positive interrelation whereas the studies of He et al (2021) and Koengkan et al (2020) confirmed negative CO 2 -GLO association. Additionally, the majority of the studies found that economic expansion triggers emissions of CO 2 (Adebayo, 2020;Coelho et al, 2021;.…”
Section: Introductionmentioning
confidence: 99%
“…However, in most developing nations, environmental regulations are not very strong, and technologies are not efficient; thus, expansion in productivity uplifts the consumption of conventional energy which in turn escalates CO 2 (Ahmed et al, 2021). These unfavorable impacts of G on environmental quality are backed by the studies of Nathaniel et al (2021) for the LCA region, Le and Ozturk (2020) for some emerging nations, Adebayo, Coelho, et al (2021) for South Korea, and Shahbaz et al (2015) for India. However, the studies Next, FI and environmental deterioration are positively associated in both Tables 6 and 7.…”
Section: Resultsmentioning
confidence: 99%